(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2023)
A bundle is a structured way of improving the processes of care and patient outcomes: a small, straightforward set of evidence-based practices-generally three to five-that, when performed collectively and reliably, have been proven to improve patient outcomes. Quality teams should resist the impulse to label any list of good changes a bundle. The power of a bundle comes from the body of science behind it and the method of execution: with complete consistency. It’s not that the changes in a bundle are new; these are well established best practices, but are often not performed uniformly, making treatment unreliable, at times idiosyncratic. A bundle ties the changes together into a package of interventions that people know must be followed for every patient, every single time. It resembles a list, but a bundle is more than that. A bundle has specific elements that make it unique. The changes are all necessary and all sufficient. It is a cohesive unit of steps that must all be completed to succeed. The changes are all based on randomized controlled trials, Level 1 evidence. They’ve been proven in scientific tests and are accepted, well-established. There should be no controversy involved, no debate or discussion of bundle elements. A bundle focuses on how to deliver the best care- not what the care should be. We want providers to get right to work on the how: on completing steps x, y, and z for every patient. The changes in a bundle are clearcut and straightforward; they involve all-or-nothing measurement. The evidences so far has proven the effectiveness of bundle approach in prevention and treatment of medical conditions. Bangladesh J Obstet Gynaecol, 2022; Vol. 37(2): 148-153